2014
DOI: 10.1039/c3ay42085j
|View full text |Cite
|
Sign up to set email alerts
|

Development, evaluation and comparison of two independent sampling and analytical methods for ortho-phthalaldehyde vapors and condensation aerosols in air

Abstract: Two independent sampling and analytical methods for ortho-phthalaldehyde (OPA) in air have been developed, evaluated and compared (1) a reagent-coated solid sorbent HPLC-UV method and (2) an impinger-fluorescence method. In the first method, air sampling is conducted at 1.0 L min−1 with a sampler containing 350 mg of silica gel coated with 1 mg of acidified 2,4-dinitrophenylhydrazine (DNPH). After sampling, excess DNPH in ethyl acetate is added to the sampler prior to storage for 68 hours. The OPA-DNPH derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…The LOD and LOQ were 0.010 and 0.033 ng/mL (corresponding to 0.050 and 0.165 ng/sample), respectively. These values are much smaller than those of the previous methods, for which LODs of 0.02 and 0.016 µg/sample, have been reported.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The LOD and LOQ were 0.010 and 0.033 ng/mL (corresponding to 0.050 and 0.165 ng/sample), respectively. These values are much smaller than those of the previous methods, for which LODs of 0.02 and 0.016 µg/sample, have been reported.…”
Section: Resultscontrasting
confidence: 64%
“…Using our procedure, the reaction yield from OPA to OPA bis‐DNPH in the extraction solution was 91%‐104% at OPA concentrations of 2.55‐509 ng/mL. Tucker reported that with the addition of excess DNPH to the DNPH‐silica cartridge, 100% recovery of OPA was realized after a storage period of 68 hours. This result suggests that the acid (DNPH) in the DNPH‐silica cartridge affects the recovery of OPA, but that the amount of excess DNPH was not sufficient to form OPA bis‐DNPH.…”
Section: Resultsmentioning
confidence: 90%
“…Bacteria can convert DMSO into dimethyl sulphide. Therefore, it should be avoided to be disposed into the sewer (Tucker, 2014). Another precaution that should be mentioned here is that DMSO should not be heated to temperatures of over 150°C, since at that threshold it will lose its thermal stability.…”
Section: Precautionsmentioning
confidence: 99%
“…HCHO was collected using an LpDNPH S10L cartridge (Supelco Inc., U.S) to contain carbonyl compounds (Williams et al, 2019). To remove the interference caused by Ozone (O 3 ), the O 3 scrubber was connected in front of the LpDNPH S10L cartridge, and the sample was collected by clicking it on a flow sampling pump (Tucker, 2014). At this time, 7.0 l of collected air in the chamber was collected at 167 ml/min, and the collected samples were stored in a cool and dark place until extraction (Even et al, 2021).…”
Section: Small Chamber Pollutant Emission Testmentioning
confidence: 99%